2018
DOI: 10.1017/jmo.2018.36
|View full text |Cite
|
Sign up to set email alerts
|

CEO outsiderness and firm performance in an emerging economy: The moderating role of managerial discretion

Abstract: Inconsistent findings from prior research on the performance consequences of new Chief Executive Officer (CEO) origin led us to study the moderating effect of managerial discretion on the link between CEO outsiderness and firms’ post-succession performance. Data from 75 CEO succession events from an emerging economy show that new CEO outsiderness, without managerial discretion context influences, has no direct impact on post-succession performance. Further, our findings emphasise the moderating impacts of mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 107 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…We usually think of the former as having lower managerial inertia and the latter as having higher managerial inertia. Many studies have also shown that managerial inertia can be detrimental to the progress and growth of a company/society (Ataay, 2020;Bel et al, 2018;Mol and Kotabe, 2011;Shen et al, 2022). From the perspective of government managers, we can see that imitative governance has influenced the government's original decision-making to some extent (Kim et al, 2018).…”
Section: Theoretical Derivationmentioning
confidence: 99%
“…We usually think of the former as having lower managerial inertia and the latter as having higher managerial inertia. Many studies have also shown that managerial inertia can be detrimental to the progress and growth of a company/society (Ataay, 2020;Bel et al, 2018;Mol and Kotabe, 2011;Shen et al, 2022). From the perspective of government managers, we can see that imitative governance has influenced the government's original decision-making to some extent (Kim et al, 2018).…”
Section: Theoretical Derivationmentioning
confidence: 99%